Aphasia friendly Canada: The aphasia friendly business campaign. Issue 2 (1st February 2022) - Borsatto, Julia; Buchanan, Lori; Pineault, Laura
ABSTRACT: Background: Aphasia creates pervasive communication barriers that make participation in society difficult. There are well over 150, 000 Canadians with aphasia, but very few people have heard of it. The consequences of this lack of knowledge is that businesses and organizations are ill-equipped to accommodate customers with this invisible disability. The present study introduces the Aphasia-Friendly Business Campaign (AFBC), which has been designed to address the lack of knowledge surrounding aphasia. This knowledge mobilization project assists businesses in increasing accessibility for people with communication disorders through business-specific training sessions. Aims: The goal was to increase awareness of aphasia in businesses and to test the efficacy of our approach. The following questions were explored: (1) Does accessibility training about aphasia and supportive communication strategies increase employee's knowledge of aphasia, and (2) do employees report increased self-efficacy in interacting with a customer with aphasia after participating in training? Method: Businesses were offered on-site aphasia training and personalized toolkits/resources were designed to accommodate the needs of people with communication disorders. Participating businesses received a training session that included a PowerPoint presentation, video examples, activity-based role-play, and an opportunity for discussion. Pre-and post-training questionnaires assessed changes in employees' declarative knowledge regarding aphasia and their perceived self-efficacy in the workplace. Results: 226 participants across 15 organizations participated in the AFBC. Participant's declarative knowledge of aphasia and perceived ability to work with people with aphasia or other communication disorders significantly improved after training. Further, the participants agreed the materials provided were adequate and helpful. Discussion and Conclusions: The increase in public knowledge regarding aphasia and the perceived ability of local employees to use supportive communication strategies have set the stage for increasing the autonomy of people with aphasia in our community. Improved public understanding of aphasia should reduce stigma surrounding the disorder, facilitate community reintegration, and improve the quality of services provided for people with aphasia. Service providers can better facilitate communication and make appropriate accommodations to assist with vocational, social and community reintegration. Future research should consider assessing longitudinal factors related to training retention and transfer (i.e., do employees remember and use these skills on the job and do they teach new employees). Further, people with aphasia in other regions of Canada continue to find their problems to be misunderstood and unaddressed by extant services, and as such, the need for the expansion of the AFBC program is necessary.